Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/mc.20261
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity triplex‐forming oligonucleotide target sequences in mammalian genomes

Abstract: Site-specific recognition of duplex DNA by triplex-forming oligonucleotides (TFOs) provides a promising approach to manipulate mammalian genomes. A prerequisite for successful gene targeting using this approach is that the targeted gene must contain specific, high-affinity TFO target sequences (TTS). To date, TTS have been identified and characterized in only approximately 37 human or rodent genes, limiting the application of triplex-directed gene targeting. We searched the complete human and mouse genomes usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
0
56
0
Order By: Relevance
“…Since that time, many groups have published reports demonstrating the ability of TFOs to inhibit the expression of a number of genes in a variety of systems. Mammalian genes that have been targeted by TFOs are summarized by Wu et al (2007) [27]. However, obstacles to this approach have limited the potential of triplex technology as a consistent and reproducible method of transcriptional regulation.…”
Section: Modulating Gene Expression Via Triplex Formationmentioning
confidence: 99%
“…Since that time, many groups have published reports demonstrating the ability of TFOs to inhibit the expression of a number of genes in a variety of systems. Mammalian genes that have been targeted by TFOs are summarized by Wu et al (2007) [27]. However, obstacles to this approach have limited the potential of triplex technology as a consistent and reproducible method of transcriptional regulation.…”
Section: Modulating Gene Expression Via Triplex Formationmentioning
confidence: 99%
“…To ensure that these targets can form stable triple helices, we require a minimum guanine rate of 50% in the purine tract of the target (Mills et al 2002;Vekhoff et al 2008). In contrast to a previous study (Wu et al 2007), however, we refrain from filtering out lowcomplexity regions since it could remove potential targets. Unique TTSs are detected using Triplexator's duplicate filter, which discards TTSs that occur more than once in the genome (either as copy or subsequence of another TTS).…”
Section: Resultsmentioning
confidence: 99%
“…Putative triplex targeting sites are located in regulatory regions, mainly promoters, carrying a potential role in gene expression regulation (Goñi et al 2004(Goñi et al , 2006Wu et al 2007;Buske et al 2012). Accordingly, it has been shown that lncRNAs are targeted to these sites, recruiting chromatin modifiers and thereby regulating gene expression (Mondal et al 2015;O'Leary et al 2015;Postepska-Igielska et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches have revealed that mammalian genomes harbor numerous TTS, which are enriched at gene promoters and regulatory elements (Goñi et al 2004(Goñi et al , 2006Wu et al 2007;Buske et al 2012). In humans and mice, there is on average one specific TTS located ∼100-200 bp upstream of transcription start sites at every 1.3 kb within the genome (Goñi et al 2004;Wu et al 2007;Buske et al 2012).…”
Section: +mentioning
confidence: 99%